DAMPAK HUKUM KEMBALINYA HAK EKONOMI KEPADA PENCIPTA PADA PERJANJIAN JUAL PUTUS ATAS LAGU DAN LIRIK - Budi Kurniawan (LP2M ISBI Bandung, 2016)
Based on the articles number 18 and 122 of Copyright Act No. 28, 2014, Sold Flat Contract will be ended in some conditions. Therefore anyEcono mic Rights of songwriter and arrangers will be transferred automatically by music producers after passing 25 ears plus 2 ears of contract, or in another case after waiting until passing to 25 years plus 2 ears if the contract has not come to an end, The legal effects with theother parties especially between music producers as copyright holders andthe third parties whose some Economic Rights and Mechanical Rights being transferred are not simple. The ending time of the contract by an Act is unusual since it is a private area. It is also an unusual term to be applied in different effect from the existing legal terms such as Null and Void, and Invalida te. This legal research will find any legal aspects caused b thesearticles application. It will also examine a preferred and suggested contractby government to transfer a copyright of license contract. In this case songwriters and arrange rs, music producer or any other parties can avoid ancircumstances indicated as an act against law in the future.